Structural changes in cow farming and milk production in Poland in 1990-2010 - Dzun, Piotr (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2012)
The subject of the paper is the process of structural changes in cow farming and milk production in Poland in 1990-2010, with special emphasis on the period of intensive systemic transformation, as well as on the pre-accession and post-accession periods. The presented analysis is based on the data from the Central Statistical Office (GUS), especially those provided by Agricultural Censuses. The results of the analysis showed that there occurred a significant decrease in the number of agricultural holdings with cows as well as in the number of cows in the examined period. However, the dynamics of such processes differed substantially in individual years. In the period of intensive systemic transformation (1990-1995) the decrease in the number of cows was larger than the decrease in the number of holdings with cows. In this period, the process of deconcentration in cow farming and regression in the improvement of cow herds became observable. Starting from the mid 1990s the decline in the number of holdings is much faster than the decline in the number of cows. Cow farming is moving to holdings with larger agrarian area. In the structure of the domestic herd, the share of herds consisting of 10 cows and more is clearly increasing. The process of concentration and specialization becomes visible. The size of average herd increases from 2.6 cows to 5.9 cows. A clear improvement occurs in terms of modernization of cow farming, milk production and quality of cow herds, which results in a higher milk yield and higher quality of milk. These processes are stimulated by intensifying competition on the milk market and growing requirements from milk processing plants. However, the level of specialization and concentration of cow farming in Poland is still low, and average milking capacity continues to be well below that recorded in the EU countries against which Poland competes on the milk market. In the coming years there will be dual-development of holdings that keep cows. Market holdings will further specialize and concentrate on cow farming, which will lead to a fast decrease in the proportion of holdings that have 20 or fewer cows. On the other hand, non-market farms, with small cow herds, will abandon such production or reduce it to the level necessary to satisfy their own needs. The rate of fall in the number of such holdings will be determined by cultural and demographic conditions rather than the economic ones.
Keywords: agrarian holdings with cows; number of cows; milk production; structure of holdings with cows; structure of cow herds; concentration and modernization of cow farming; regional diversification